The impact of liberalization on higher education and domestic regulation - Nik Mahmod, Nik Ahmad Kamal; Tham,, Siew Yean; Alavi, Rokiah (2011)
Free Trade Agreements are gaining increasing popularity as trade policy instruments, especially in East Asia. The number of concluded FTAs in Asia as a group increased from only 3 in 2000 to 54 in 2009, while 40 of these agreements are currently in effect. Another 78 FTAs are currently under negotiations or proposed. Bilateral FTAs comprise 74% of the concluded FTAs while the remainder agreements are plurilateral in nature. Hence it is likely that FTAs in Asia will continue to proliferate and dominate the governance of international trade. At the regional level, the Association of Southeast Asian countries (ASEAN) is emerging as the hub for Asian FTAs. It is thus expected that regional and bilateral trade agreements will play the key roles in trade liberalization and increasing market access for the near future, particularly since the stalled World Trade Organization (WTO)‟s Doha Round does not seem to be heading toward a significant conclusion. Malaysia to date has concluded four bilateral agreements with Japan, Pakistan, New Zealand and Chile while she is negotiating another four with Turkey, European Union, Australia and the Trans Pacific Partnership (TPP). At the regional level, Malaysia is also a member of the ASEAN‟s extra regional agreements with China, Japan, Korea, Australia, New Zealand and India. In view of the increasing number of bilateral agreements and the importance of the higher education sector to the country as a new growth sector, this study aims to examine the impact of liberalization on this sector as well as the domestic regulations that govern the sector. Specifically, the study has the following research objectives; • Assess the current commitments and their impact on the Malaysian market and domestic private providers. • Assess the impact on market access for Malaysian providers in partner countries for the FTAs that have been concluded thus far. • Assess the impact on domestic regulations. Based on the analysis in these three areas, the study will provide some assessment on the impact of liberalization on foreign direct investment (FDI) and capacity building; quality and recognition; as well as access, equity and distribution.